War in peace paramilitary violence in Europe after the Great War - Gerwarth, Robert 1976-; Horne, John 1949- (The Greater War, 2012)
Paramilitarism in Europe after the Great War: an introduction / Robert Gerwarth and John Horne -- PART I: REVOLUTION AND COUNTER-REVOLUTION -- The syndrome of violence in Russia's civil wars, 1918-1920 / William G. Rosenberg -- Bolshevism as fantasy: fear of revolution and counter-revolutionary violence, 1917-23 / Robert Gerwarth and John Horne -- Fighting the red beast: counterrevolutionary violence in the defeated states of central Europe / Robert Gerwarth -- Revolution, civil war, and terror in Finland in 1918 / Pertti Haapala and Marko Tikka -- Paramilitary violence in Italy: the rationale of fascism and the origins of totalitarianism / Emilio Gentile -- PART II: NATIONS, BORDERLANDS, AND ETHNIC VIOLENCE -- Bands of nation builders? Insurgency and ideology in the Ukrainian civil war / Serhy Yekelchyk -- Turning citizens into soldiers: Baltic paramilitary movements after the Great War / Tomas Balkelis -- The origins, attributes and legacies of paramilitary violence in the Balkans / John Paul Newman -- Paramilitary violence in the collapsing Ottoman Empire / Uğur Ümit Ungör -- Soldiers to civilians, civilians to soldiers: Poland and Ireland after the first world war / Julia Eichenberg -- The British culture of paramilitary violence in the Irish War of Independence / Anne Dolan -- Defending victory: paramilitary politics in France, 1918-26. A counter-example / JOhn Horne